If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2z + -0.9 = 3z Reorder the terms: -0.9 + 2z = 3z Solving -0.9 + 2z = 3z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-3z' to each side of the equation. -0.9 + 2z + -3z = 3z + -3z Combine like terms: 2z + -3z = -1z -0.9 + -1z = 3z + -3z Combine like terms: 3z + -3z = 0 -0.9 + -1z = 0 Add '0.9' to each side of the equation. -0.9 + 0.9 + -1z = 0 + 0.9 Combine like terms: -0.9 + 0.9 = 0.0 0.0 + -1z = 0 + 0.9 -1z = 0 + 0.9 Combine like terms: 0 + 0.9 = 0.9 -1z = 0.9 Divide each side by '-1'. z = -0.9 Simplifying z = -0.9
| .5-3x=18.5 | | 3x^2-5x-13=0 | | 9.8-6.45h=127.835 | | 2n/2=30 | | 2(z-1)=-84 | | 4(12)=-48 | | .4x+.5=.6x+.7+.8x | | 10m+2m=8 | | -3(1-3x)=2(-4x+7) | | 5(3X-1)-9X=2(4X+11)-2X | | 36m+4= | | -2(y+4)=2y | | 9=-11*5x | | -40=-3x-7 | | .5-.7= | | -2x^2+25x+100=0 | | -7f+3=-32 | | -3x+15= | | 8(-8+v)=-160 | | 31=4m+7 | | 17-20p=4(-13-5p) | | 5x-6=11x-12 | | 17w+17= | | 7(n-1)=-35 | | 8x+9=3x-16 | | 12+2x=13-3x | | 3p+8=7 | | 150=-10-8n | | 6x+4x-68=51-7x | | m+623=814 | | 2z-4-z=-2 | | 10c+5=-195 |